2018
DOI: 10.1371/journal.pone.0197113
|View full text |Cite
|
Sign up to set email alerts
|

Severe neonatal hyperbilirubinemia induces temporal and occipital lobe seizures

Lian Zhang

Abstract: To examine the origin of seizures induced by severe neonatal hyperbilirubinemia, The EEG characteristics of seizures were analyzed in newborns with and without severe neonatal hyperbilirubinemia. Fisher’s exact test was used to determine the specificity. In total, 931 patients had a total serum bilirubin (TSB) level of 340–425 μmol/L, only 2 of whom had seizures. Compared to patients with hyperbilirubinemia and a TSB level of 340–425 μmol/L, those with a TSB level >425 μmol/L had a significant risk of seizure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…neurons is not uncommon among newborns with jaundice. [22][23][24][25][26]44 Our results suggest that early severe abnormalities in aEEG recordings are correlated with neurological deficits in newborns with severe jaundice, although its sensitivity was only 35.7%, which was very low compared with abnormal ABR with a sensitivity of 83.3%. One reason for this result might be that ABE might be reversible with rapid and aggressive intervention.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…neurons is not uncommon among newborns with jaundice. [22][23][24][25][26]44 Our results suggest that early severe abnormalities in aEEG recordings are correlated with neurological deficits in newborns with severe jaundice, although its sensitivity was only 35.7%, which was very low compared with abnormal ABR with a sensitivity of 83.3%. One reason for this result might be that ABE might be reversible with rapid and aggressive intervention.…”
Section: Discussionmentioning
confidence: 67%
“…Bilirubin damages both neurons and astrocytes 3,17 and typically affects the basal ganglia and subthalamus, 3,18,19 which are closely correlated with the electrical activity of cortical neurons. [20][21][22] Previous research using conventional electroencephalography (EEG) has identified diverse abnormal courses of EEG patterns under varying degrees of hyperbilirubinemia in term neonates. 23,24 For example, video EEG in newborns with jaundice clearly predicts the onset of seizures in the temporal and occipital lobes of newborns with total serum bilirubin (TSB) levels greater than 340 mmol/L (17.1 mmol/L ¼ 1 mg/dL of bilirubin; thus 340 mmol/L ¼ 19.9 mg/ dL).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal jaundice can be a leading cause of morbidity if treated improperly [ 2 ]. It can also lead to serious complications such as temporal and occipital lobe seizures in its severe forms [ 3 ], as well as kernicterus and potentially permanent neuro-developmental delay [ 4 ].…”
Section: Introductionmentioning
confidence: 99%